Qualitative methods in business research - Eriksson, Päivi; Kovalainen, Anne (SAGE Publications Ltd, 2016)
Covering all the major qualitative approaches in business research (including case study research, ethnography, narrative inquiry, discourse analysis, grounded theory and action research), this practical, how-to guide shows how qualitative methods are used within management, marketing and organizational studies